Survival dan Maturitas Guru Agama Islam Pada Era Revolusi Industri 4.0 di Masa Pandemi Covid 19 - Ahmad Rivauzi; Rengga Satria; Wirdati Wirdati; Murniyetti Murniyetti; Muhammad Kosim (Jurnal Kawakib, 2021)
In the era of the Industrial Revolution 4.0 and the disaster of the COVID-19 pandemic has changed the human life. Humans are required to change their life perspective. The spirit is needed to survive, accompanying change, and is expected to become a locomotive for the changing of life and turn the obstacle become oportunities. This research was descriptive qualitative research. It describe the resilience and maturity of Islamic religious teachers in the industrial revolution 4.0 era and during the covid 19 pandemic. The survival and maturity of religious teachers can be seen from their activities in AGPAII. Islam as a religion revealed by Allah has the values ​​that immunize its adherents to survive and even become pioneers in their lives and civilizations. Through the AGIL analysis approach, this research shows that religious teachers who are well prepared and can survive, can be seen from the quantity and types of AGPAII activities during the Covid 19 pandemic. Religious values ​​play a strategic role to survive and to adapt and even be able to produce creative innovations